How do key audit matter characteristics combine to impact financial statement understandability?. (2nd June 2021) - Ong, Sau Yu; Moroney, Robyn; Xiao, Xinning
Abstract: The intention behind the communication of key audit matters (KAMs) is to facilitate financial statement understandability by providing information about the focus of the audit. We predict and find two KAM characteristics affecting financial statement understandability: readability and quantification. While KAM readability enhances financial statement understandability, quantification impacts understandability in different ways. When a KAM is more readable, quantification further enhances understandability, but when a KAM is less readable, understandability is lower when quantification is present than when absent. Our findings suggest that KAMs are more helpful to investors when readable and quantification is more beneficial when KAMs are readable.